Approximation Theorems for q-Bernstein-Kantorovich Operators - Mahmudov, N. I.; Sabancigil, P. (Univ Nis, Fac Sci Math, 2013)
In the present paper we introduce a q-analogue of the Bernstein-Kantorovich operators and investigate their approximation properties. We study local and global approximation properties and Voronovskaja type theorem for the q-Bernstein-Kantorovich operators in case 0 < q < 1.
Keywords: q-integers; positive operator; q-Bernstein-Kantorovich operator